ANALISA MERKURI (Hg) PADA SEDIMEN SUNGAI AEK GANTANG DI KECAMATAN HUTABARGOT, KABUPATEN MANDAILING NATAL SUMATERA UTARA - Widiastuti, Dewi W; Marpaung, Nalom D; Wardana, M. Eka (LPPM ISTP, 2025)
The analysis of mercury (Hg) in the sediments river of the Aek Gantang’s river in Hutabargot District, Mandailing Natal Regency, North Sumatra has been conducted. The objective of this research is to determine the Hg content in river sediments to understand its pollution potential. The method used is observational, and data analysis is performed using qualitative descriptive analysis. The Hg content analysis was conducted using the USEPA 3050B/USEPA245.7 method. The parameters used are based on ANZECC/ARMCANZ with a threshold value of 0.15-1.0 ppm. The Hg content obtained in the river sediments at the Aek Kaporas location, before any gold mining activity, was 0.042 ppm, while at the downstream location after gold mining activities in Aek Gantang, it was 0.203 ppm. The results show that small-scale mining activities can increase the Hg content in river sediments when compared to the standards.